Overall Dynamic Body Acceleration in Straw-Colored Fruit Bats Increases in Headwinds but Not With Airspeed - O'Mara, M. Teague; Scharf, Anne K.; Fahr, Jakob; Abedi-Lartey, Michael; Wikelski, Martin; Dechmann, Dina K. N.; Safi, Kamran (Frontiers in Ecology and Evolution, 2019)
Atmospheric conditions impact how animals use the aerosphere, and birds and bats should modify their flight to minimise energetic expenditure relative to changing wind conditions. To investigate how free-ranging straw-coloured fruit bats (Eidolon helvum) fly with changing wind support, we use data collected from bats fit with GPS loggers and an integrated triaxial accelerometer and measure flight speeds, wingbeat frequency, and overall dynamic body acceleration (ODBA) as an estimate for energetic expenditure. We predicted that if ODBA reflects energetic expenditure, then we should find a curvilinear relationship between ODBA and airspeed consistent with aerodynamic theory. We expected that bats would lower their airspeed with tailwind support and that ODBA will decrease with increasing tailwinds and increase with wingbeat frequency. We found that wingbeat frequency has the strongest positive relationship with ODBA. There was a small, but negative, relationship between airspeed and ODBA, and bats decreased ODBA with increasing tailwind. Bats flew at ground speeds of 9.6 ± 2.4 ms-1 (mean ± sd, range: 4.3 to 23.9 ms-1) and airspeeds of 10.2 ± 2.5 ms-1, and did not modify their wingbeat frequency with speed. Free-ranging straw-coloured fruit bats therefore exerted more total ODBA in headwinds but not when they changed their airspeed. It is possible that the flexibility in wingbeat kinematics may make flight of free-ranging bats less costly than currently predicted or alternatively that the combination of ODBA and airspeed at our scales of measurement does not reflect this relationship in straw-coloured fruit bats. Further work is needed to understand the full potential of free-ranging bat flight and how well bio-logging techniques reflect the costs of bat flight.